Analysis of Judges' Considerations in Cases of Murder Based on Infidelity - Sidiq, Fahmi; Ibrahim, Riza Andrian; binti Abdullah Suhaimi, Nurnisaa (Communication in Research and Publications (CRP), 2023)
This study discusses the judge's consideration in deciding the criminal case of murder based on infidelity based on the judge's consideration of Article 338 of the Criminal Code Decision Number 88/Pid.B/2022/PN. The research uses normative juridical methods by examining primary and secondary legal materials. The results showed that the judge's consideration included both juridical and non-juridical aspects that influenced the final decision. The defendant is considered accountable for his actions, taking into account various factors such as the confession of guilt, the defendant's attitude in the trial, and previous legal experience. In addition, the defendant's actions and their impact on victims and society are also important factors in the judge's deliberations.